Evaluation of the Application of LQR and LQT Methods for DC Motor Control in Improving Energy Efficiency in the Maritime Community Electrical System with MATLAB Simulink Application - Hardanis Firdaus Murfi (Politeknik Perkapalan Negeri Surabaya, 2024)
This study aims to investigate the wave characteristics generated by the Linear Quadratic Regulator (LQR) and Linear Quadratic Tracking (LQT) control systems, implemented on a PitmanExpress™ DC motor model 14207S007. The research methodology is based on simulations, starting with the acquisition of the mathematical model data of the DC motor in the form of a transfer function. The second set of data required includes the motor's state-space values, which are then converted into variables for MATLAB programming. These two sets of data are integrated into a unified system consisting of LQR or LQT subsystems, with first-order or second-order configurations, within the MATLAB SIMULINK application. Following data acquisition from the simulation scope results, the system is subjected to noise disturbances to assess the robustness of the control systems. This paper focuses on evaluating the effectiveness of LQR and LQT methods when applied to DC motors, particularly in the context of improving energy efficiency in community-driven projects, such as those in maritime communities. These methods are expected to contribute to energy sustainability and cost reduction in local energy management systems, supporting the development of sustainable energy solutions in rural and coastal areas. The findings from this study are aimed at community empowerment by introducing innovative, energy-efficient solutions that can be adopted by maritime communities to reduce dependency on non-renewable energy sources, ultimately improving the economic stability of such communities.